2007
DOI: 10.1111/j.1475-6773.2007.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Hospital Utilization among the Uninsured Near Elderly: Data and Policy Implications for West Virginia

Abstract: The specific needs of the near elderly warrant consideration in WV's (and other states') ongoing development and evaluation of policies aimed at reducing uncompensated care costs, including programs to expand access to health insurance and primary and mental health care among the uninsured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Moreover, in areas without safety-net health systems, the uninsured and other vulnerable people may have to utilize non-safety-net providers, which has serious financial implications for healthcare systems, communities, and states [28]. A study of hospital discharges in West Virginia found that uninsured near-older adults were more likely to be admitted for emergency conditions, to have comorbidities, complications, and longer hospital stays, and to incur higher charges (constituting 30% of all uninsured charges) [29]. Their self-pay and charity care charges were also higher than for any other adult age group [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in areas without safety-net health systems, the uninsured and other vulnerable people may have to utilize non-safety-net providers, which has serious financial implications for healthcare systems, communities, and states [28]. A study of hospital discharges in West Virginia found that uninsured near-older adults were more likely to be admitted for emergency conditions, to have comorbidities, complications, and longer hospital stays, and to incur higher charges (constituting 30% of all uninsured charges) [29]. Their self-pay and charity care charges were also higher than for any other adult age group [29].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The prevalence of multiple risk factors for heart disease and stroke is highest among people with the lowest household incomes (52.5%), and almost twice as high as the prevalence of those with the highest household income (28.8%). 9 Individuals who are uninsured are substantially more likely to be hospitalized for a preventable condition, 10,11 or to be diagnosed with a later-stage cancer. 12,13 Regardless of income level, lack of health insurance is associated with decreased use of recommended health care services for cancer prevention, cardiovascular risk reduction, and diabetes management.…”
Section: The Problemmentioning
confidence: 99%
“…25 Reasons for expeditious placement are likely related to delayed healthcare access in rural settings resulting in greater illness severity upon presentation. 26-33 Barriers to healthcare access and greater co-morbidity burden may also explain why the uninsured were more likely to require emergent CVC during their hospital visit. 31-33 Irrespective of the exact causes, populations traditionally challenged by access to the healthcare system may be more likely to require early CVC placement.…”
Section: Discussionmentioning
confidence: 99%